2016
DOI: 10.21077/ijf.2016.63.2.49952-16
|View full text |Cite
|
Sign up to set email alerts
|

Growth and mortality parameters of Sillago sihama (Forsskal, 1775) in coastal waters of the Hormozgan Province, Iran

Abstract: NoteGrowth and mortality parameters of Sillago sihama (Forsskal, 1775) ABSTRACTMonthly total length frequency data of silver sillago Sillago sihama were collected from the coastal waters of Hormozgan Province, Persian Gulf, from July 2011 to July 2012. ELEFAN-I module of FISAT II was used to analyse the length frequency data. The length-weight relationship derived, demonstrated that growth in this species is allometric. The asymptotic length (L∞) was estimated as 26 and 30 cm for males and females, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Fishing in the wild is difficult for this species because it usually swims fast and burrows into the sand to escape the catch. Unfortunately, it has been reported that the species declined in the world, such as the southern Taiwan Strait, the Northern Bay, the Hormozgan Province and Persian Gulf (Liu, Zhu, & Huo‐Sheng, ; Lu, Chen, & Du, ; Safaie, Alizadeh, Kamrani, & Momeni, ). Owing to the successful artificial propagation technologies of S .…”
Section: Introductionmentioning
confidence: 99%
“…Fishing in the wild is difficult for this species because it usually swims fast and burrows into the sand to escape the catch. Unfortunately, it has been reported that the species declined in the world, such as the southern Taiwan Strait, the Northern Bay, the Hormozgan Province and Persian Gulf (Liu, Zhu, & Huo‐Sheng, ; Lu, Chen, & Du, ; Safaie, Alizadeh, Kamrani, & Momeni, ). Owing to the successful artificial propagation technologies of S .…”
Section: Introductionmentioning
confidence: 99%
“…However, the S . sihama has been overexploited in some areas of the world, such as the Hormozgan Province, Persian Gulf (Safaie, Alizadeh, Kamrani & Momeni, ), the southern Taiwan Strait (Lu, Chen & Du, ), and the Beibu Gulf (Liu, Zhu & Huo‐Sheng, ). In recent years, the first batch of artificial breeding of S .…”
Section: Introductionmentioning
confidence: 99%
“…S. sihama, acting as common marine food fish in China (Guo et al, 2014), is beneficial to invalids and children (Mckay, 1992) due to its abundant omega-3 fatty acid, protein, and calcium content. However, the S. sihama has been overexploited in some areas of the world, such as the Hormozgan Province, Persian Gulf (Safaie, Alizadeh, Kamrani & Momeni, 2016), the southern Taiwan Strait (Lu, Chen & Du, 2008), and the Beibu Gulf (Liu, Zhu & Huo-Sheng, 2010). In recent years, the first batch of artificial breeding of S. sihama has been successfully finished in Guangdong Ocean University, which inspired people to farm it.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is common along the Indian and Asian coast extending to Taiwan and common throughout the Philippines, Indonesian Archipelago and as far as northern Australia (Carpenter & Niem, ; Mckay, ; Sheaves, ). However, decrease in resources has been reported in Persian Gulf, Beibu Gulf and Taiwan Strait (Liu, Zhu, & Lu, ; Lu, Chen, & Du, ; Safaie, Alizadeh, Kamrani, & Momeni, ). In recent years, environmental pollution and overfishing have brought heavy threat for this species in Chinese waters (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%